Odpowiedzi

2010-03-18T09:22:39+01:00
1.
x²+3 = x(x+1)+2 +2
x²+3 = x²+x+2+2
-x = 4-3
-x = 1
x = -1

2.
a)x+2/9+x-1/3=1
2x = 1+1/3-2/9
2x = 4/3-2/9
2x = 10/9 /:2
x = 10/18
x = 5/9

b)2x+3/5=2-x/3+x
2x+x/3-x = 2-3/5 /*15
30x+5x-15x = 30-9
20x = 21
x = 21/20



c)3x-5/2-5x-1/10=0
3x-5x = 1/10+5/2
-2x = 26/10 /: -2
x = -26/20
x = -13/10

d)x/2=2/5(4-x)-4
x/2 = 8/5-2/5x-4 /*10
5x = 16-4x-40
5x+4x = 16-40
9x = -24
x = -24/9
x = -8/3

e)2x-1/5-x-2/2=0,7x
2x-x-0,7x = 1/5+1
0,3x = 6/5 /:0,3
x = 60/15
x = 4


f)2x-3x+5/4=-1/4x-1
-x+1/4x = -1-5/4
-3/4x = -9/4 /:-3/4
x = 9/3
x = 3
1 5 1
2010-03-18T09:39:49+01:00
1. Oblicz wartość x
a) wartość wyrażenia x²+3 jest o 2 większa od wartości wyrażenia x(x+1)+2

x²+3-2=x(x+1)+2
x²+1=x²+x+2
x²-x²-x=2-1
-x=1 /*-1
x=1


2.Rozwiąż równania.
a)x+2/9+x-1/3=1 /*9
9x+2+9x-3=9
18x=10 /18
x=10/18 = 5/9

b)2x+3/5=2-x/3+x /*15
30x+9=30-5x+15x
20x=21 /20
x= 1 1/20


c)3x-5/2-5x-1/10=0 /*10
30x-25-50x-1=0
-20x=26 /-20
x= -26/20 = -1 3/10


d)x/2=2/5(4-x)-4 /*10
5x=4(4-x)-40
5x=16-4x-40
9x=-24 /9
x = - 2 2/3

e)2x-1/5-(x-2)/2=0,7x /*10
20x-2-5x+10=7x
8x=-8 /8
x=-1


f)2x-3x+5/4=-1/4x-1 /*4
8x-12x+5=-x-4
-3x=-9 /-3
x=3

1 5 1